Diagnostic evaluation of pleural fluid: the role of total protein and lactic dehydrogenage - Rahman, Md Sayedur; Siddiqui, Md Abdul Moyeed; Rabbani, Md Golam; Nazimuddin, Md; Al-Farooque, Abdullah; Hasan, SM Mahmudul; Bhuiyan, Md Abdul Quddus; Ara, Mah Jabeen (Journal of Armed Forces Medical College, Bangladesh, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> doi:10.3329/jafmc.v4i2.1839 JAFMC Bangladesh Vol.4(2) 2008 18-20